Dynamics of mobilization and professional development in Hondurans formally employed abroad - Venegas Figueroa, Carlos; Salgado-Guifarro, Onix (LACCEI, 2025)
The migration of professionals, known as "brain drain," represents a growing phenomenon with significant implications for developing countries, particularly Honduras. This qualitative study aimed to analyze the experiences of young Honduran professionals who have migrated abroad for formal employment opportunities, examining how this mobility contributes to their professional development and human capital utilization, as well as the impact on their country of origin. Through semi-structured interviews, it was identified that education in Honduras provided a foundation, but it was the experience abroad that allowed for significant human capital enrichment, with the acquisition of new competencies in dynamic environments. Motivations for migration are multifactorial, including the search for better working conditions, professional development, and quality of life, in contrast to the scarcity of opportunities and low wages in Honduras. The impact is ambivalent: while migrants experience personal and professional growth and contribute through remittances, the direct application of their enriched human capital for Honduras’s development is limited due to the lack of return plans and persistent conditions in the country.